The Influence of The Number of Windings on Torque And Power of A 250w Electric Motor on An Electric Bicycle - Dananjoyo, Ajitiyo; Fahrudin, A’rasy (International Journal on Orange Technologies, 2025)
Everyone uses transportation as a means of getting to different locations. There are three categories for the actual modes of transportation: air, sea, and land. People typically use ground transportation, such buses, cars, and bicycles, for daily errands and commutes to the office since these modes of transportation are more convenient and quick to use. The electric bicycle is one of the vehicles that is currently being developed. The development of electric bicycles is necessary since they are simple and comparatively inexpensive to produce. Naturally, an electric bicycle needs a motor to propel it. A DC motor needs a voltage that enters the field coil in the same direction in order to generate mechanical energy. Electromotive force is produced by the armature coil while magnetic force is produced by the field coil. When the armature coil current interacts with the magnetic field, it produces the torque (T) that powers the motor. A DC motor has windings, and the quantity of windings in the motor can change its torque and output. The author of this study employs a DC motor, and alterations are planned to the windings through both an increase and a decrease in winding count. The objective is to ascertain how a 250W electric motor's torque and power are affected by the number of windings. According to the study's findings, the torque and power obtained at the start of the standard winding test were 0.55 and 5.7, respectively, when the RPM reached 100.4. When the rpm hits 77.8, adding coils results in a torque of 0.55 and a power of 4. When the rpm reaches 131.3 and the torque is 5.5, the power is 7.5 after the coils are reduced. Thus, the rpm and power generated decrease with the number of windings. Both the resulting rpm and the power released are inversely proportional to the reduced winding.